Do Women Give Up Competing More Easily? Evidence from Speedcubers - Chao Fang; Ernest Zhang; Junfu Zhang (Institute of Labor Economics (IZA), 2021)
We analyze a large sample of participants in mixed-gender Rubik's Cube competitions. Focusing on participants who barely made or missed the cut for the second round in a competition, we examine their likelihood of joining another competition in the future. We find a significant gender difference: Whereas boys are slightly discouraged by failing to qualify for the second round, girls are affected more and are more likely to give up forever. Furthermore, we find that this gender difference is most significant in countries with larger gender gaps in labor market outcomes.
Keywords: D91; J16; L83; 330; gender gap; competition; Rubik's Cube